Business Vitality Initiative : Facilitator Handbook - Community Economic Development and Employability Corporation (CEDEC) (2010)
The Purpose of this Manual: The BVI includes two highly structured public meetings which require expert facilitation. This manual is a basic resource for facilitators. Other necessary resources include: • The BVI PowerPoint presentation • The BVI Community Handbook • Discussions with CIEL management • Discussions with the Community Sponsor • A BVI Assessment Report and Final Report from another community